THE EFFECT OF SOCIAL MEDIA ON RELIGIOUS BEHAVIOR, SOCIAL INTERACTION, AND MENTAL HEALTH OF STUDENTS IN ISLAMIC EDUCATION IN THE DIGITAL AGE - Azmat Sadik, Aulia; Fattah, Abdul; Ulviani, Maria (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: In the digital era, social media has become a dominant force shaping how students communicate, express religious identity, and experience mental well-being. Purpose: This study investigates the influence of social media on three interrelated dimensions—religious behavior, social interaction, and mental health—among students in Islamic education. Method: Employing a quantitative correlational method, data were collected from 96 students at MTs Muhammadiyah Panaikang, South Sulawesi, using structured Likert-scale questionnaires. Data analysis was conducted through Pearson correlation tests and descriptive statistics. Result: The findings show a moderate positive correlation (r = 0.48, p < 0.05) between social media use and religious behavior, indicating that online Islamic content may reinforce students’ spiritual practices. A strong positive correlation (r = 0.62, p < 0.01) was also found between social media and social interaction, highlighting its role in strengthening peer communication and digital community building. Conversely, a moderate negative correlation (r = –0.55, p < 0.01) emerged between social media and mental health, suggesting that excessive use contributes to stress, anxiety, and emotional fatigue. These findings underscore the dual role of social media as both an enabler of digital religiosity and a source of psychological strain. Conclusion: The study concludes that while social media offers educational and spiritual benefits, its overuse necessitates the integration of digital literacy and ethical guidance grounded in Islamic values. Educators are encouraged to embed Islamic digital ethics and mental health awareness into the curriculum to promote balanced online engagement. Future research should explore long-term behavioral patterns and develop integrative digital ethics frameworks suited to Islamic educational settings.